Dietary freshwater clam (Corbicula fluminea) extract suppresses accumulation of hepatic lipids and increases in serum cholesterol and aminotransferase activities induced by dietary chloretone in rats. Issue 7 (3rd July 2015) - Chijimatsu, Takeshi; Umeki, Miki; Kobayashi, Satoru; Kataoka, Yutaro; Yamada, Koji; Oda, Hiroaki; Mochizuki, Satoshi
Abstract: We investigated the ameliorative effect of freshwater clam extract (FCE) on fatty liver, hypercholesterolemia, and liver injury in rats exposed to chloretone. Furthermore, we examined the effects of major FCE components (fat and protein fractions) to determine the active components in FCE. Chloretone increased serum aminotransferase activities and led to hepatic lipid accumulation. Serum aminotransferase activities and hepatic lipid content were lower in rats fed total FCE or fat/protein fractions of FCE. Expression of fatty acid synthase and fatty acid desaturase genes was upregulated by chloretone. Total FCE and fat/protein fractions of FCE suppressed the increase in gene expression involved in fatty acid synthesis. Serum cholesterol levels increased twofold upon chloretone exposure. Total FCE or fat/protein fractions of FCE showed hypocholesterolemic effects in rats with hypercholesterolemia induced by chloretone. These suggest that FCE contains at least two active components against fatty liver, hypercholesterolemia, and liver injury in rats exposed to chloretone. Graphical abstract: : Freshwater clam extract (FCM) suppresses accumulation of hepatic lipids and liver cell injury induced by xenobiotics.